The Influence of Social Media for Millennials in the Digital Age - Fathan Awalur Rayyan (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2022)
In the era of technology 4.0 which is growing, almost all fields have used the internet and have become a necessity in everyday life, both among children, millennials, adults, the elderly, the elderly and so on. Including social media which has a very big influence in everyone's life. Someone who initially does not understand technology with the existence of social media becomes aware, and social media can also change a person's attitude and nature. In the community, especially millennials, social media has become a necessity that cannot be separated from everyday life and has become a lifestyle where millennials do not spend a day without opening social media. If it is explored further in depth during its development period, millennials need direction and guidance both at school, at home and in the surrounding environment because millennials are still looking for their identity by hanging out with friends their age. The purpose of this study is to determine the positive and negative impacts of social media, to know the characteristics of social media, to know the types of social media, and to understand what the millennial generation is like. The results of this study increase creativity, means of communication, facilitate communication, a place for achievement, a place for learning media. While the negative impacts of social media such as misuse of technology, decreased focus on learning, high crime rates, cyberbullying. The specific characteristics of Social Media include: Reach, Accessibility, Use, Actuality, Persistence. Classification of Social Media include: Collaborative projects (Wikipedia), Blogs and microblogs (twitter), Content (youtube), Social networking sites (Facebook), Virtual game world (online games), Victure social world (second life). Millennial Generation itself When viewed from the age group, the millennial generation is a generation that is currently aged between 15-34 years..